Offshore is a form, not a place: paradoxes, global spaces and global classes in offshoring finance and detention. Issue 1 (2nd January 2018) - Chambers, Peter
ABSTRACT: This paper shows why offshore is a form, not a place, by observing our implication in offshoring finance and detention. This is undertaken through a systems theorization that examines and compares two offshoring processes: Euromarket's production of xenomarkets and Australian border security's offshoring of the mainland continent. Applications of offshore's form produce paradoxes and hierarchies, indicating carefully designed political effects that allow us to pinpoint the spaces and class relations characterizing global spaces at the heart of the political present, and the labour and methods of their making.